Assistance in Organic Waste Management Using Maggots, Biopores, and Composters in Jatirejoyoso Village - Izzalqurny, Tomy Rizky; Yanto, Alif Faruqi Febri; Pahrany, Andi Daniah; Ferdiansyah, Rifaldy Adinandra (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Jatirejoyoso Village in Kepanjen Subdistrict struggles with organic waste management due to its proximity to a market and extensive agricultural activities. This community service program aims to revolutionize waste management by introducing maggot cultivation, biopore holes, and composters within a circular economy framework. The goal is to enhance the community's capacity to manage waste efficiently, reduce pollution, and create new economic opportunities through the production of maggots, fertilizers, and compost. Method: The project started with field observations and a Forum Group Discussion (FGD) to identify needs and strategies. Continuous training and assistance were provided in maggot cultivation, biopore creation, and composting, with Standard Operating Procedures (SOPs) involving farmer groups and the village community. Practical Application: Key technologies implemented include maggot cultivation for high-quality animal feed, biopore holes to support waste management and improve soil absorption, and composters to produce organic fertilizers. Conclusion: The program successfully reduced organic waste and boosted the community’s economic well-being, equipping them with the skills to manage waste sustainably, benefiting both the environment and the local economy.